Immune cells drive new immunomodulatory therapies for myocardial infarction: From basic to clinical translation - Nian, Wenjian; Huang, Zijian; Fu, Cong (Frontiers in Immunology, 2023)
The high incidence of heart failure secondary to myocardial infarction (MI) has been difficult to effectively address. MI causes strong aseptic inflammation, and infiltration of different immune cells and changes in the local inflammatory microenvironment play a key regulatory role in ventricular remodeling. Therefore, the possibility of improving the prognosis of MI through targeted immunity has been of interest and importance in MI. However, previously developed immune-targeted therapies have not achieved significant success in clinical trials. Here, we propose that the search for therapeutic targets from different immune cells may be more precise and lead to better clinical translation. Specifically, this review summarizes the role and potential therapeutic targets of various immune cells in ventricular remodeling after MI, especially monocytes/macrophages and neutrophils, as a way to demonstrate the importance and potential of immunomodulatory therapies for MI. In addition, we analyze the reasons for the failure of previous immunomodulatory therapies and the issues that need to be addressed, as well as the prospects and targeting strategies of using immune cells to drive novel immunomodulatory therapies, hoping to advance the development of immunomodulatory therapies by providing evidence and new ideas.